2015
DOI: 10.3758/s13414-015-0956-8
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the controversy of the proportion validity effect: Volitional attention is not required, but may have an effect

Abstract: Response time (RT) is facilitated when a target appears at a cued (valid) location versus an uncued (invalid) location. Interestingly, this valid-versus-invalid RT difference increases as the percentage of valid trials increases. In the present study, we investigated the mechanism responsible for this proportion valid cueing effect (PVE). The PVE is thought to reflect changes in voluntary attentional allocation, with greater attention being committed endogenously to the cued location as the percentage of valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…With the current explicit cues, we observe RTs that are comparable across spatial certainty conditions for valid cues, whereas RTs on invalid trials increase as spatial certainty decreases. We inspected the previous literature and observed that this is a consistent finding across other studies that varied the probabilities of explicit spatial cues in comparable tasks (Lanthier et al, 2015;Vossel et al, 2006) , suggesting that this is a replicable phenomenon, rather than the consequence of a ceiling effect or something similar. In contrast, Stankevich and Geng (2014) observed the opposite; RTs decreased as target location became more likely (analogous to valid trials) but remained invariant when directed towards increasingly less likely (invalid) locations.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…With the current explicit cues, we observe RTs that are comparable across spatial certainty conditions for valid cues, whereas RTs on invalid trials increase as spatial certainty decreases. We inspected the previous literature and observed that this is a consistent finding across other studies that varied the probabilities of explicit spatial cues in comparable tasks (Lanthier et al, 2015;Vossel et al, 2006) , suggesting that this is a replicable phenomenon, rather than the consequence of a ceiling effect or something similar. In contrast, Stankevich and Geng (2014) observed the opposite; RTs decreased as target location became more likely (analogous to valid trials) but remained invariant when directed towards increasingly less likely (invalid) locations.…”
supporting
confidence: 72%
“…However, our interest here is how endogenous (learned) spatial associations interact with other learned associations, specifically value associations to control visual selection. Strong evidence that spatial cueing effects (both endogenously and exogenously driven) depend on learning is that they scale with the reliability of the cue (Lanthier et al, 2015;Vossel et al, 2006Vossel et al, , 2015 , being stronger when cues are more predictive and weaker when predictability is low. Indeed, cueing effects appear to be a linear function of the certainty gained (in bits of information) by a spatial cue (Prinzmetal et al, 2015) .…”
mentioning
confidence: 99%
“…It is also possible that a form of statistical learning gave rise to the attentionalcapture effects by color in Experiment 3 (cf. Lanthier et al, 2015). In any case, the magnitude of the validity effect of the task-irrelevant target colors was clearly smaller than the effects with cues of a task-relevant color in Experiments 1 and 2.…”
Section: Discussionmentioning
confidence: 63%
“…Maybe the color-based cueing effect in Experiment 3 reflected an implicit form of learning of color-target associations that is different from priming and more akin to statistical learning (cf. Lanthier, Wu, Chapman, & Kingstone, 2015). Such implicit attentional guidance might not lead to the incorporation of the target-associated feature into the top-down set of explicitly instructed relevant target features.…”
Section: Discussionmentioning
confidence: 99%
“…Our interest here is how endogenous (learned) spatial associations interact with other learned associations, specifically value associations to control visual selection. Strong evidence that spatial cueing effects depend on learning is that they scale with the reliability of the cue (Lanthier et al, 2015;Vossel et al, 2006Vossel et al, , 2015, being stronger when cues are more predictive and weaker when predictability is low. Indeed, cueing effects appear to be a linear function of the certainty gained (in bits of information) by a spatial cue (Prinzmetal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%